Birth Outcomes in Women With Body Mass Index of 40 kg/m2 or Greater Stratified by Planned and Actual Mode of Birth: A Systematic Review and Meta-Analysis. Issue 4 (22nd December 2021) - D'Souza, R.; Horyn, I.; Jacob, C.-E.; Zaffar, N.; Horn, D.; Maxwell, C.
Abstract : ( Acta Obstet Gynecol Scand . 2021;100:200–209) Obese pregnant women are at increased risk of complications compared to those with normal body mass index (BMI). One systematic review found that pregnant women with BMI ≥40 kg/m 2 were more likely to experience prepregnancy diabetes, gestational diabetes or hypertensive disorders during pregnancy compared with those with BMI ≤30 to 39.9 kg/m 2 . Among other factors, these conditions have been linked to higher rates of cesarean delivery (CD) and wound complications. Obesity in pregnancy has also been associated with increased risk of neonatal complications including Apgar scores <7 after 5 minutes and birth trauma. Vaginal delivery (VD) has generally been accepted as the preferred mode of delivery for this population. The aim of this study was to evaluate outcomes in obese pregnant women based on mode of delivery.